RISK FACTORS FOR PULMONARY TUBERCULOSIS INCIDENCE IN THE WORK AREA OF THE PUBLIC HEALTH CENTER IN PALEMBANG - Mardanila, Mardanila; Maksuk, Maksuk; Esti Sri Ananingsih (Indonesia Epidemiological Journal, 2025)
Background: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. This disease is still a health problem in Indonesia, especially in the work area of the Sekip Health Center. Objective: To determine the risk factors for Pulmonary Tuberculosis in the working area of the Sekip Health Center, Palembang City. Method: This study uses a cross-sectional design with purposive sampling.technique. The population of the study was all patients with Pulmonary TB and suspects, with a sample of 103 respondents. Results: The majority of patients with Pulmonary TB were found in the average age group of 49 years, with male sex (8.7%) and income ≤ minimum wage (48.5%). The incidence of pulmonary TB was significantly related to occupancy density (p=0.011), ventilation area (p=0.041), lighting (p=0.043), humidity (p=0.048), and temperature (p=0.044). Behavioral factors of contact history (0.010) and smoking habit (p=0.040). Based on the results of the Chi-Square test, it was found that there was a significant relationship with the incidence of pulmonary TB. Conclusion: The incidence of pulmonary TB was found in a small number of people living in the work area of the Public Health Center in Palembang, namely occupancy density, ventilation area, lighting, humidity, temperature, contact history, and smoking habits. Therefore, it is necessary to make efforts for the community to maintain the home environment and implement Clean and healthy living.Behavior (CHLB), and conduct early examinations for those who have a history of contact to prevent the transmission of pulmonary TB.